Isolation of molybdenum-reducing bacterium; Serratia sp. strain MIE2 from agriculture soil and its potential use in soil bioremediation - Halmi, Mohd Izuan Effendi; Wan Johari, Wan Lutfi; Mohd Ali, Mohd Shukuri; Shaharuddin, Noor Azmi (Hibiscus Publisher, 2017)
Molybdenum is reported to be very toxic to ruminants and shows evidence of spermatogenesistoxicity in animals and insects. Hence, its removal is important. In this study, we report on thefirst isolation of molybdenum-reducing bacterium from agricultural soil. The bacterium reduceshexavalent molybdenum (sodium molybdate) to molybdenum blue (Mo-blue); a colloidalproduct, which can be trapped and removed from solution. Phylogenetic analysis resulted in atentative identification of the bacterium as Serratia sp. strain MIE2. The optimum conditions forMo-blue production using the normal one-variable-at-a-time (OVAT) approach were 10 mM ofsodium molybdate, pH 6.0, a temperature of 35°C, ammonium sulphate at 10 g/L as the nitrogensource and sucrose concentrations of between 30-50 g/L as the carbon source and electron donorfor molybdate. Studies on the effects of pesticides and solvents on Mo-blue production showedthat Mo-blue production from whole cells was relatively more affected by these xenobioticscompared to the crude enzyme. Nevertheless, the strain was resistant to most of the xenobioticstested. Based on the strain MIE characteristics, the bacterium will be a suitable candidate for theremediation of aquatic bodies and agricultural soils contaminated with molybdenum.